Shrinkage Stresses in Dried Materials - Kowalski, S.J.; Musielak, G.; Rybicki, A. (Engineering Transactions, 1992)
The aim of the paper is to analyse the shrinkage stresses in isotropic material when they do not exceed its strength. The model established in author's previous work is used for describing the problem undertaken. The model relates stresses with strains, moisture content and temperature, The state of dried material is described by a system of five differential equations with double coupling. Their solution must satisfy additionally the compatibility relations. The problem of convectively dried plate is solved as an example. The evolution of both the moisture content and the shrinkage stresses distributions as well as the deformation of the plate during drying process were determined. The finite difference method and the method of separation of variables were used and good agreement of the results obtained on the basis of these two methods were stated. They are presented on graphs.